Consumer Discrimination and Self-Employment - Borjas, George J.; Bronars, Stephen G. (Journal of Political Economy, 1989)
Self-employment rates and incomes differ significantly by race. We show that these differentials arise in markets with consumer discrimination and incomplete information about the price of the good and the race of the seller. Equilibrium income distributions have two properties: mean black incomes are lower than mean white incomes, and the returns to ability are lower for black than for white sellers. Able blacks, therefore, are less likely to selfselect into the self-employment sector than able whites. Using the 1980 Census data, we find that observed differences in the self-employment income distributions are consistent with the theoretical predictions.